(untitled) (Communications in Computational Physics, 2010)
To obtain fine distributing calculation about the time, space and energy of neutron flux for a kind of non-stationary particle transport problem, the scheme of global Monte Carlo variance reduction is developed. In order to provide the foundation for this scheme, it is necessary to analyze its effectiveness before putting it to use. This paper fulfills this through analyzing the effectiveness of its core which is Monte Carlo transport importance biased calculation. By decomposing the arithmetic and calculating the representative objectives, the effectiveness of the Monte Carlo transport importance biased calculation is demonstrated.